2007
DOI: 10.1002/jcp.21123
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of IGFBP‐2 proteolysis is attenuated with progression to androgen insensitivity in the LNCaP progression model

Abstract: The identification of molecular determinants involved in the promotion of metastasis and development of androgen insensitive prostate cancer (AI-PCa) is necessary to discriminate aggressive from indolent disease and to identify therapeutic targets for advanced disease. Overexpression of one particular member of the insulin like growth factor (IGF) axis, IGFBP-2, is implicated in the development of AI-PCa and other cancers. Using the LNCaP human PCa progression model, we show that the AI and metastatic prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…IGFBP-2 protein is degraded by proteases such as matrix metalloprotease-1 and -7, calpain, as well as by basic fibroblast growth factor and an androgen blockade. [61][62][63][64] We found IGFBP-2 protein was degraded by a treatment of PI3K inhibitor in A549 cells. Because a various new PI3K inhibitors have been entered clinical trials, 65 IGFBP-2 would be a useful biomarker for the treatment with PI3K inhibitors in lung cancer as well as in glioma, prostate, and breast cancers.…”
Section: Discussionmentioning
confidence: 75%
“…IGFBP-2 protein is degraded by proteases such as matrix metalloprotease-1 and -7, calpain, as well as by basic fibroblast growth factor and an androgen blockade. [61][62][63][64] We found IGFBP-2 protein was degraded by a treatment of PI3K inhibitor in A549 cells. Because a various new PI3K inhibitors have been entered clinical trials, 65 IGFBP-2 would be a useful biomarker for the treatment with PI3K inhibitors in lung cancer as well as in glioma, prostate, and breast cancers.…”
Section: Discussionmentioning
confidence: 75%
“…In addition to IGFBP-2 expression being associated with advanced prostate cancer and bone metastasis [102], IGFBP-2 also appears to be linked with the development of hormone refractory prostate cancer. As reported by DeGraff et al [103], androgen treatment in the LNCaP prostate cancer cell line (derived from metastatic site left supraclavicular Lymph Node; androgen sensitive; AS), initially increases the levels of IGFBP-2, but with extended androgen treatment levels, decreases via mechanisms likely to involve proteolysis of IGFBP-2. Interestingly, when the androgen insensitive (AI) and metastatic prostate cancer cell lines C4e2B4 and C4-2 (LNCaP derived) were investigated, it was found that these cells express a greater amount of IGFBP-2 and exhibit an attenuated ability to proteolyse extracellular IGFBP-2.…”
Section: Igfbp-2 and Prostate Cancermentioning
confidence: 72%
“…Western blotting analysis was performed as reported previously [25]. Briefly, cell lysates were prepared with Complete Lysis-M kit (Roche, Nutley NJ) as per manufacture protocol and protein concentrations were determined via standard BCA protocol (Pierce, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%